2021
DOI: 10.1021/acs.macromol.1c01229
|View full text |Cite
|
Sign up to set email alerts
|

Sequence–Conformation Relationship of Zwitterionic Peptide Brushes: Theories and Simulations

Abstract: Zwitterionic polymer brushes have broad applications in antifouling, biolubrication, and drug delivery. The charge distribution on polymers is critical to the structure and properties of surface-tethered zwitterionic polymer brushes. However, there is a lack of understanding of the relationship between the charge distribution and conformation in these systems, which is important for designing and predicting the functionality of controllable surface-tethered polymer brushes. Zwitterionic peptides with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…The MD simulations (Figures S1 and S2) revealed that PHHP maintains a more stable secondary structure compared to ZIP, as supported by residue contact maps and the Ramachandran plot (Figures S3 and S4), indicating that the unique polyhydroxyproline helical structure of PHHP effectively retains its rigidity, while ZIP tends to adopt folded and disordered conformations due to its flexibility. 5,17 Furthermore, a 100 ns MD simulation (Figures S5 and S6) affirmed that PHHP exhibits a stable backbone with minimal fluctuations, while ZIP demonstrates structural instability and higher flexibility, especially in its terminal residues, consistent with previous observations. 7 The hydrophilicity of a peptide is critical in assessing its antifouling effect, as it affects the formation of the protective hydration layer.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The MD simulations (Figures S1 and S2) revealed that PHHP maintains a more stable secondary structure compared to ZIP, as supported by residue contact maps and the Ramachandran plot (Figures S3 and S4), indicating that the unique polyhydroxyproline helical structure of PHHP effectively retains its rigidity, while ZIP tends to adopt folded and disordered conformations due to its flexibility. 5,17 Furthermore, a 100 ns MD simulation (Figures S5 and S6) affirmed that PHHP exhibits a stable backbone with minimal fluctuations, while ZIP demonstrates structural instability and higher flexibility, especially in its terminal residues, consistent with previous observations. 7 The hydrophilicity of a peptide is critical in assessing its antifouling effect, as it affects the formation of the protective hydration layer.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…The presence of salt bridges served as an indication of the potential impact of ion− peptide interactions on the peptide's overall behavior and characteristics, encompassing electrical properties and structure, surpassing simple adsorption. 17 Indeed, the analysis of the adsorption of Fe 3+ with ZIP indicated that the strongest adsorption occurs due to coordination interactions between Fe 3+ and the carboxyl groups of the peptide. This coordination interaction was visually represented in Figure S11D, highlighting the specific binding sites and the formation of coordination complexes between Fe 3+ ions and the carboxyl groups in ZIP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockcharged peptides prefer loop and head-to-tail structures upon surface attachment whereas alternating-charged peptide prefer extended and parallel structures with dense brush structures; consequently, alternately-charged peptides performed better in antifouling applications. [55] Peptides can also be tuned to bind to specific targets via the use of biorecognition sequences, including specific types of polymers or other biomaterials relevant for surface functionalization to create a more stable anti-fouling layer than would be achieved by simple physicochemical interactions. For example, Date et al used a polyetherimide-specific polymer-binding peptide to observe the effect of peptide density on the further attachment of functional proteins to the surface.…”
Section: Hydration Layer-supporting Peptidesmentioning
confidence: 99%
“…21 Various computational and theoretical approaches have been applied to investigate the influence of monomer sequence and other variables on the properties of PABs. [22][23][24][25][26] However, these studies have focused on sequence-controlled PABs with strong acid and base chemistries in which the monomers remain fully ionized under typical solution conditions or employed methods that assume fixed monomer charge states. By contrast, PABs with weakly acidic and basic monomers exhibit changes in their charge state due to variations in pH a Department of Chemical and Biomolecular Engineering, University of Houston, and salt concentration and hence enhanced brush responses that can be harnessed to design smart surfaces.…”
Section: Introductionmentioning
confidence: 99%